Didymodon mongolicus (Bryophyta, Pottiaceae), a new species from Mongolian Plateau (Bangladesh Journal of Plant Taxonomy, 2016)
Didymodon mongolicus D. P. Zhao &T. R. Zhang is described as a new species from northern China and Mongolia. The new taxon is distinguished from others species of the genus by its small, ovate leaves, weakly recurved margins, smooth laminal cells and costa ending several cells below the apex, with 1 layer of ventral stereids in the lower part of the leaf. Drawings and light microscope photographs of the main characters are given, and its relationships with some closely related species within the genus are discussed.Bangladesh J. Plant Taxon. 23(2): 175-180, 2016 (December)